Lipid nanostructures for antioxidant delivery: a comparative preformulation study - Esposito, Elisabetta; Sguizzato, Maddalena; Drechsler, Markus; Mariani, Paolo; Carducci, Federica; Nastruzzi, Claudio; Valacchi, Giuseppe; Cortesi, Rita (Beilstein Journal of Nanotechnology, 2019)
This investigation is a study of new lipid nanoparticles for cutaneous antioxidant delivery. Several molecules, such as α-tocopherol and retinoic acid, have been shown to improve skin condition and even counteract the effects of exogenous stress factors such as smoking on skin aging. This work describes the design and development of lipid nanoparticles containing antioxidant agents (α-tocopherol or retinoic acid) to protect human skin against pollutants. Namely, solid lipid nanoparticles and nanostructured lipid carriers were prepared using different lipids (tristearin, compritol, precirol or suppocire) in the presence or absence of caprylic/capric triglycerides. The formulations were characterized by particle size analysis, cryogenic transmission electron microscopy, small-angle X-ray diffraction, encapsulation efficiency, preliminary stability, in vitro cytotoxicity and protection against cigarette smoke. Nanostructured lipid carriers were found to reduce agglomerate formation and provided better dimensional stability, as compared to solid lipid nanoparticles, suggesting their suitability for antioxidant loading. Based on the preformulation study, tristearin-based nanostructured lipid carriers loaded with α-tocopherol were selected for ex vivo studies since they displayed superior physico-chemical properties as compared to the other nanostructured lipid carriers compositions. Human skin explants were treated with α-tocopherol-loaded nanostructured lipid carriers and then exposed to cigarette smoke, and the protein levels of the stress-induced enzyme heme oxygenase were analyzed in skin homogenates. Interestingly, it was found that pretreatment with the nanoformulation resulted in significantly reduced heme oxygenase upregulation as compared to control samples, suggesting a protective effect provided by the nanoparticles.
Keywords: α-tocopherol; cryogenic transmission electron microscopy (cryo-TEM); dermocosmetics; HO-1; nanostructured lipid carriers (NLCs); retinoic acid; skin pollution; solid lipid nanoparticles (SLNs)

(untitled) - Rembiesa, J.; Ruzgas, T.; Engblom, J.; Holefors, A. (Cosmetics, 2018)

(untitled) - Saha, S. P.; Bhalla, D. K.; Whayne, T. F.; Gairola, C. G. (Int. J. Angiol., 2007)

(untitled) - Onor, I. O.; Stirling, D. L.; Williams, S. R.; Bediako, D.; Borghol, A.; Harris, M. B.; Darensburg, T. B.; Clay, S. D.; Okpechi, S. C.; Sarpong, D. F. (Int. J. Environ. Res. Public Health, 2017)

(untitled) - Kennedy, C.; Bastiaens, M. T.; Willemze, R.; Bouwes Bavinck, J. N.; Bajdik, C. D.; Westendorp, R. G. J. (J. Invest. Dermatol., 2003)

(untitled) - Silvano, A.; Nistri, S.; Calosi, L.; Romagnoli, P. (Ital. J. Anat. Embryol., 2019)

(untitled) - Suehara, L. Y.; Simone, K.; Maia, M. (An. Bras. Dermatol., 2006)

(untitled) - Hu, S. S.; Neff, L.; Agaku, I. T.; Cox, S.; Day, H. R.; Holder-Hayes, E.; King, B. A. (Morb. Mortal. Wkly. Rep., 2016)

Handbook of Experimental Pharmacology - Benowitz, N. L.; Hukkanen, J.; Jacob, P., III (Nicotine Chemistry, Metabolism, Kinetics and Biomarkers)

(untitled) - Bruno, R. S.; Traber, M. G. (J. Nutr., 2005)

(untitled) - Bruno, R. S.; Leonard, S. W.; Atkinson, J.; Montine, T. J.; Ramakrishnan, R.; Bray, T. M.; Traber, M. G. (Free Radical Biol. Med., 2006)

(untitled) - Alberg, A. J. (Toxicology, 2002)

(untitled) - Thomsen, S. F.; Sørensen, L. T. (Skin Therapy Lett., 2010)

(untitled) - Handelman, G. J.; Packer, L.; Cross, C. E. (Am. J. Clin. Nutr., 1996)

(untitled) - Dietrich, M.; Block, G.; Norkus, E. P.; Hudes, M.; Traber, M. G.; Cross, C. E.; Packer, L. (Am. J. Clin. Nutr., 2003)

(untitled) - Mistry, N. (Cosmetics, 2017)

(untitled) - Wolf, G. (J. Nutr., 2005)

(untitled) - Buettner, G. R. (Arch. Biochem. Biophys., 1993)

(untitled) - Chen, J.; Wei, N.; Lopez-Garcia, M.; Ambrose, D.; Lee, J.; Annelin, C.; Peterson, T. (Eur. J. Pharm. Biopharm., 2017)

(untitled) - Vaz, S.; Silva, R.; Amaral, M. H.; Martins, E.; Sousa Lobo, J. M.; Silva, A. C. (Colloids Surf., B, 2019)

(untitled) - Okuno, M.; Kojima, S.; Matsushima-Nishiwaki, R.; Tsurumi, H.; Muto, Y.; Friedman, S.; Moriwaki, H. (Curr. Cancer Drug Targets, 2004)

(untitled) - Ross-Innes, C. S.; Stark, R.; Holmes, K. A.; Schmidt, D.; Spyrou, C.; Russell, R.; Massie, C. E.; Vowler, S. L.; Eldridge, M.; Carroll, J. S. (Genes Dev., 2010)

(untitled) - Uray, I. P.; Dmitrovsky, E.; Brown, P. H. (Semin. Oncol., 2016)

(untitled) - Xue, Y.; Harris, E.; Wang, W.; Baybutt, R. C. J. (J. Biomed. Sci. (London, U. K.), 2015)

(untitled) - Andersen, F. A. (Int. J. Toxicol., 2002)

(untitled) - MacGregor, J. L.; Maibach, H. I. (Exog. Dermatol., 2002)

(untitled) - Saez, V.; Souza, I. D. L.; Mansur, C. R. E. (Int. J. Cosmet. Sci., 2018)

(untitled) - Eiras, F.; Amaral, M. H.; Silva, R.; Martins, E.; Lobo, J. M. S.; Silva, A. C. (Int. J. Pharm., 2017)

(untitled) - Castro, G. A.; Oréfice, R. L.; Vilela, J. M. C.; Andrade, M. S.; Ferreira, L. A. M. (J. Microencapsulation, 2007)

(untitled) - Kumar, S.; Randhawa, J. K. (Mater. Sci. Eng., C, 2013)

(untitled) - Pardeike, J.; Hommoss, A.; Müller, R. H. (Int. J. Pharm., 2009)

(untitled) - Üner, M.; Yener, G. (Int. J. Nanomed., 2007)

(untitled) - Jores, K.; Mehnert, W.; Drechsler, M.; Bunjes, H.; Johann, C.; Mäder, K. (J. Controlled Release, 2004)

(untitled) - Müller, R. H.; Mäder, K.; Gohla, S. (Eur. J. Pharm. Biopharm., 2000)

(untitled) - Jenning, V.; Thünemann, A. F.; Gohla, S. H. (Int. J. Pharm., 2000)

(untitled) - Dingler, A.; Gohla, S. (J. Microencapsulation, 2002)

(untitled) - Paliwal, R.; Babu, R. J.; Palakurthi, S. (AAPS PharmSciTech, 2014)

(untitled) - Esposito, E.; Drechsler, M.; Mariani, P.; Carducci, F.; Servadio, M.; Melancia, F.; Ratano, P.; Campolongo, P.; Trezza, V.; Cortesi, R.; Nastruzzi, C. (Biomed. Microdevices, 2017)

(untitled) - Pecora, R. (J. Nanopart. Res., 2000)

(untitled) - Esposito, E.; Fantin, M.; Marti, M.; Drechsler, M.; Paccamiccio, L.; Mariani, P.; Sivieri, E.; Lain, F.; Menegatti, E.; Morari, M.; Cortesi, R. (Pharm. Res., 2008)

(untitled) - Kulkarni, C. V. (Nanoscale, 2012)

(untitled) - Puglia, C.; Bonina, F.; Rizza, L.; Cortesi, R.; Merlotti, E.; Drechsler, M.; Mariani, P.; Contado, C.; Ravani, L.; Esposito, E. (J. Pharm. Sci., 2010)

Aultons’s Pharmaceutics-The design and manufacture of the medicines - Pugh, W. J. (Churchil Livingstone Elsevier, 2007)

(untitled) - Esposito, E.; Sticozzi, C.; Ravani, L.; Drechsler, M.; Muresan, X. M.; Cervellati, F.; Cortesi, R.; Valacchi, G. (Exp. Dermatol., 2015)

(untitled) - Muresan, X. M.; Sticozzi, C.; Belmonte, G.; Savelli, V.; Evelson, P.; Valacchi, G. (Mech. Ageing Dev., 2018)

(untitled) - Muresan, X. M.; Sticozzi, C.; Belmonte, G.; Cervellati, F.; Ferrara, F.; Lila, M. A.; Valacchi, G. (Arch. Biochem. Biophys., 2018)

(untitled) - Valacchi, G.; Pecorelli, A.; Belmonte, G.; Pambianchi, E.; Cervellati, F.; Lynch, S.; Krol, Y.; Oresajo, C. (J. Invest. Dermatol., 2017)

Virtual Computational Chemistry Laboratory, ALOGPS 2.1

NCBI homepage U.S. (National Library of Medicine National Center for Biotechnology Information)

(untitled) - Abraham, N. G.; Kappas, A. (Pharmacol. Rev., 2008)

(untitled) - Atzori, L.; Caramori, G.; Lim, S.; Jazrawi, E.; Donnelly, L.; Adcock, I.; Barnes, P. J.; Chung, K. F. (Respir. Med., 2004)